Student Tuition Fee Management Using Web-Based Application System - Dahlan Susilo; Muhammad Dwi Nugroho; Diyah Ruswanti (TEPIAN, 2023)
Access to global information online is essential for an institution or group. Users who use web-based apps from their homes or other locations may meet their requirements without traveling to the designated institution. This study aims to determine if stakeholders' demands can be met by the web-based application for tuition fee management at the Islamic boarding school "Bilal Bin Rabah" in Sukoharjo. Both documentation and UML (Unified Modeling Language) modeling techniques were employed in this study. The purpose of this application is to make it simpler for administrative staff to handle information on student fee payments and to evaluate financial information for associated parties. Three people may use this application's payment system: the administrator, the head of the Islamic boarding school, and a parent of a student. The administrator may handle student information, and payment information, charge the student’s parents, and print the necessary reports for the Islamic Boarding School. The school's headmaster has access to student data and may generate reports and examine student invoices. The invoices and transaction history of payments that have been made are visible to parents/guardians of students. The website will continue to be developed to support the mobile platform, allowing users to access the school fee management system via mobile more conveniently. Based on the test results, users of the SPP payment system application are quite satisfied.